Extragenital Mycoplasma genitalium infections among men who have sex with men. (19th June 2019) - Latimer, Rosie Louise; Vodstrcil, Lenka; De Petra, Vesna; Fairley, Christopher K; Read, Tim RH; Williamson, Deborah; Doyle, Michelle; Chow, Eric PF; Bradshaw, Catriona
Abstract : Objectives: There are limited data on the prevalence of Mycoplasma genitalium (Mgen) coinfection with rectal chlamydia ( Chlamydia trachomatis (CT)) and rectal gonorrhoea ( Neisseria gonorrhoeae (NG)) infections and few studies examining the prevalence of pharyngeal Mgen in men who have sex with men (MSM). Using transcription-mediated amplification assay, this study aimed to determine the proportion of rectal CT and rectal NG infections in MSM who are coinfected with rectal Mgen, and the proportion of MSM with Mgen detected in the pharynx in order to inform clinical practice. Methods: This was a cross-sectional study conducted at Melbourne Sexual Health Centre in Australia. Consecutively collected rectal swabs from MSM that tested positive for CT (n=212) or NG (n=212), and consecutively collected pharyngeal samples (n=480) from MSM were tested for Mgen using the Aptima Mycoplasma genitalium Assay (Hologic, San Diego). Samples were linked to demographic data and symptom status. Results: Rectal Mgen was codetected in 27 of 212 rectal CT (13%, 95% CI 9 to 18) and in 29 of 212 rectal NG (14%, 95% CI 9 to 19) samples, with no difference in the proportion positive for Mgen. MSM with rectal CT/Mgen coinfection had more sexual partners than those with rectal CT monoinfection (mean 6 vs 11, p=0.06). MSM with rectal NG/Mgen coinfection were more likely to be HIV-positive than those with rectal NG monoinfection (OR=2.96, 95% CI 1.21 to 7.26, p=0.023). MSM with rectal CT/Mgen coinfection were more likely to be using pre-exposure prophylaxis than MSM with rectal NG/Mgen coinfection (OR 0.25, 95% CI 0.10 to 0.65, p=0.002). Pharyngeal Mgen was uncommon and detected in 8 of 464 samples (2%, 95% CI 1% to 3%). Pharyngeal Mgen was associated with having a rectal STI (OR=10.61, 95% CI 2.30 to 48.87, p=0.002), and there was a borderline association with being HIV-positive (p=0.079). Conclusion: These data indicate one in seven MSM treated for rectal CT or rectal NG will have undiagnosed Mgen that is potentially exposed to azithromycin during treatment of these STIs. Rectal Mgen coinfection was associated with specific risk factors which may inform testing practices. Pharyngeal Mgen was uncommon.